2021
DOI: 10.1080/17453674.2021.1879505
|View full text |Cite
|
Sign up to set email alerts
|

Reoperations after decompression with or without fusion for L4–5 spinal stenosis with or without degenerative spondylolisthesis: a study of 6,532 patients in Swespine, the national Swedish spine register

Abstract: Background and purpose — There are different opinions on how to surgically address lumbar spinal stenosis with concomitant degenerative spondylolisthesis (DS). We investigated reoperation rates at the index and adjacent levels after L4–5 fusion surgery in a large cohort of unselected patients registered in Swespine, the national Swedish spine register. Patients and methods — 6,532 patients, who underwent surgery for L4–5 spinal stenosis with or without DS between 2007 and 2012, were followed up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…After removing duplicates and screening the titles and abstracts for the remaining articles, 81 full-text articles were evaluated. Ultimately, 33 studies (6 RCTs 7 , 8 , 19 , 20 , 21 , 22 and 27 cohort studies 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ) involving 94 953 participants were included in this study.
Figure 1 Literature search and screening process.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After removing duplicates and screening the titles and abstracts for the remaining articles, 81 full-text articles were evaluated. Ultimately, 33 studies (6 RCTs 7 , 8 , 19 , 20 , 21 , 22 and 27 cohort studies 11 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ) involving 94 953 participants were included in this study.
Figure 1 Literature search and screening process.
…”
Section: Resultsmentioning
confidence: 99%
“…Our results are consistent with those of many previous studies. 9 , 10 , 23 , 25 , 42 With regards to the included studies, the common reasons for reoperation in decompression alone group were same-segment disease (including disc herniation and recurrent stenosis), while the main reasons for reoperation in the fusion group were implant-related problems and adjacent-segment stenosis and instability. 7 , 39 Long-term follow-up results showed that although spinal fusion accelerated the degeneration of adjacent segments, it had no effects on clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A negative consequence of fusion is that it accelerates the degenerative process in the segments proximal to the fusion construction, the so-called Adjacent Segment Disease (ASD) 35,36 . Past studies have found high percentage of ASD and reoperation rate after DF 37–39 . Risk factors for ASD after fusion have been shown to be LSS as the indication for fusion and high age 40 .…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Past studies have found high percentage of ASD and reoperation rate after DF. [37][38][39] Risk factors for ASD after fusion have been shown to be LSS as the indication for fusion and high age. 40 Therefore, it is not uncommon for patients who have previously undergone fusion for LSS with DS, to present with new degeneration and stenosis of the proximal adjacent level.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, spine surgeons may presume that slippage and dynamic instability at the level of spondylolisthesis are better treated with fusion (2). However, there have been lingering controversies reported in several studies regarding these two surgical options (8,9). Previous studies have shown that superior clinical results were achieved when fusion was added to decompression in patients with LSS + DS (10,11).…”
Section: Introductionmentioning
confidence: 99%